Diversity and horticultural grouping in Capsicum spp. - AHMAD, K P SUNIL, RASHEED (Journal of Spices and Aromatic Crops, 1998)
One hundred and sixty chilli (Capsicum) accessions maintained at Chalode (Kerala, India) were assigned to five species. The 128 C. annuum lines identified were assigned to 3 varietal groups and 12 horticultural groups. The characteristics and importance of the taxonomic groups identified are discussed in respect to selection, and intervarietal and interspecific hybridisation in chilli.